A user-centred approach to irrigation performance: drip irrigation in the Khrichfa area, Morocco. Issue 7 (3rd October 2017) - van der Kooij, Saskia; Kuper, Marcel; Zwarteveen, Margreet Z.; de Fraiture, Charlotte M. S.
ABSTRACT: Conventional irrigation performance assessments narrowly confine the possible effects of using drip irrigation to what it is designed to do, i.e., improve efficiencies. While helpful in the design, such assessments leave little scope for the possibility that irrigators adopt the technology for reasons other than improving efficiencies. Using a case study about how irrigators in the farmer-managed Khrichfa Canal in Morocco engaged with drip irrigation, we propose a user-centred approach to irrigation performance. Use of this approach opens up the possibility that a technology is used and mobilized for other reasons than only those intended in the design process.